Microglia-Derived Exosomes Improve Spinal Cord Functional Recovery after Injury via Inhibiting Oxidative Stress and Promoting the Survival and Function of Endothelia Cells. (26th August 2021) - Peng, Wei; Wan, Liyang; Luo, Zixiang; Xie, Yong; Liu, Yudong; Huang, Tingmo; Lu, Hongbin; Hu, Jianzhong
Abstract : Traumatic spinal cord injury (SCI) is a devastating disease of the central nervous system with long-term disability and high mortality worldwide. Revascularization following SCI provides nutritional supports to rebuild and maintain the homeostasis of neuronal networks, and the subsequent promotion of angiogenesis is beneficial for functional recovery. Oxidative stress drastically produced following SCI has been contributed to endothelial dysfunction and the limited endogenous repair of microvasculature. Recently, exosomes, being regarded as potential therapeutic candidates for many kinds of diseases, have attracted great attentions due to its high bioavailability, safety, and stability. Microglia have been reported to exhibit proangiogenic function and guide the forming of vasculature during tissue repair. However, the specific role of microglia-derived exosomes (MG-Exos) played in SCI is still largely unknown. In the present study, we aimed to evaluate whether MG-Exos could protect spinal cord microvascular endothelial cells (SCMECs) against the toxic effects of oxidative stress, thus promote SCMECs' survival and function. We also investigated the protective effects of MG-Exos in the mouse model of SCI to verify their capability. Our results demonstrated that MG-Exo treatment significantly decreased the level of oxidative stress (ROS), as well as did the protein levels of NOX2 when bEnd.3 cells were exposed to H2 O2 -induced oxidative stress in vitro and in vivo . Functional assays showed that MG-Exos could improve the survival and the ability of tube formation and migration in H2 O2 -induced bEnd.3 in vitro . Moreover, MG-Exos exhibited the positive effects on vascular regeneration and cell proliferation, as well as functional recovery, in the mouse model of SCI. Mechanically, the keap1/Nrf2/HO-1 signaling pathway was also investigated in order to unveil its molecular mechanism, and the results showed that MG-Exos could increase the protein levels of Nrf2 and HO-1 via inhibiting the keap1; they also triggered the expression of its downstream antioxidative-related genes, such as NQo1, Gclc, Cat, and Gsx1 . Our findings indicated that MG-Exos exerted an antioxidant effect and positively modulated vascular regeneration and neurological functional recovery post-SCI by activating keap1/Nrf2/HO-1 signaling.